Effects of Service Quality Management on Performance of Vernacular Radio Broadcasting Firms in Western Kenya - Awino, Beatrice Akoth; Ondoro, Charles Omondi; Abong’o, Beatrice Evelyn (European Scientific Journal, ESJ, 2018)
Managing the quality of products and services is very important in ensuring that business excels in meeting its customer requirements and achieves organizational goals. Recent studies around service quality management cover quality management and total quality management in various contexts. However, knowledge on effect of service quality management on performance of vernacular radio firms is lacking. This study explored the effect of service quality management on performance of vernacular radio broadcasting firms in western Kenya. The study adopted explanatory research design on 16 vernacular radio stations from the western region of Kenya covering the Nyanza and Western Counties. Primary data was collected and analysed descriptively. The study revealed that service quality management positively and significantly predicts performance of vernacular radio broadcasting firms in Western Kenya (β = 0.839, p<0.05). The regression weight value of 0.839 implies that an increase of 1 standard deviation in the management of service quality is likely to lead to an increase of 0.839 standard deviations in performance of vernacular radio broadcasting firms. The study concluded that service quality management has a positive and significant effect on the performance of vernacular radio broadcasting firms in western Kenya, and accounts for up to 70.4% of the variation in firm performance.